O-283 Evidence based management of endometriosis – what has changed since 2013?. (30th June 2022) - Becker, C; Bokor, A; Heikinheimo, O; Horne, A; Jansen, F; Kiesel, L; King, K; Kvaskoff, M; Nap, A; Petersen, K; Saridogan, E; Tomassetti, C; et al.
Abstract: In 2005, under the auspices of ESHRE, a group of international experts evaluated the existing best evidence and published the first European guideline on the management of endometriosis. This highly successful project was the first guideline by ESHRE and was adopted by many counties as their national standard. A second, fully-updated edition was presented in 2013. For the new ESHRE Endometriosis Guideline, published in February 2022, all available evidence for twelve chosen topics was gathered by a senior research specialist. Subgroups comprised of patient representatives and experts in healthcare, reproductive science and epidemiology evaluated the data according to GRADE criteria. Each subgroup wrote a chapter and formulated their recommendations which were then presented by a representative to the core group. There, a provisional document was generated and made available for stakeholder review. The resulting comments were taken into account and where relevant incorporated into the final guideline document for which approval was sought and gained from the ESHRE Executive Committee. 35 PICO (Patients, Interventions, Comparison, Outcome) and seven narrative questions were addressed resulting in 78 Research Recommendations were formulated. Where sufficient scientific evidence was lacking and the Guideline Development Group (GDG) was of the opinion that an important topic needed to be highlighted Good Clinical Practice Points where created based on experts' experience. During the process of reviewing the literature it became apparent that large knowledge gaps of the best clinical approach to endometriosis exist. As a result, 30 research recommendations were also produced. One of the main differences to the 2013 version of the ESHRE guidelines is that laparoscopy is no longer the gold standard for endometriosis per se as there exist sufficient data to support the use of transvaginal ultrasound performed by an experienced operator or MRI can equally identify or rule out ovarian and most of deep endometriosis. However, it is recognised by the GDG that the required imaging standards are not ubiquitously available and for peritoneal disease both sensitivity and specificity using either imaging modalities are still poor. As opposed to the 2013 recommendation, the GDG does not anymore recommend an ultralong protocol for the women with rASRM stage III/IV endometriosis to improve IVF success rates. Furthermore, gonadotropin releasing hormone antagonists seem to be effective in the treatment of endometriosis-associate pain and, where available, could be considered as second-line treatment. Other changes were specific chapters on endometriosis in adolescents and in menopausal women as the GDG strongly felt that these groups are concerningly underrepresented in clinical care and research. Finally, a chapter focussing on the association of endometriosis with certain forms of cancer namely subgroups of ovarian cancer, breast and thyroid cancer was added to give both patients and clinicians a better insight into the current evidence of this complex topic. The GDG hope that the new ESHRE Endometriosis Guideline will improve the clinical management of a highly prevalent and heterogenous disease and that the freely-available patient-friendly version of the guideline empowers symptomatic and asymptomatic women to seek the best available advice, support and treatment.